CONTRIBUTIONS AGILITY, RESILIENCE AND SELF-CONFIDENCE AGAINST BALL DRIBBLING SKILLS (DRIBBLING) FUTSAL - Darmawan, Fiat Dodi; Sulaiman, Sulaiman; Setyawati, Heny (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The purpose of this study was to analyze the contribution of agility, endurance and confidence in dribbling skills futsal SMAN 4 Purwokerto. How big is the contribution of each factor and combination of several of these factors to dribble skills.The method used is quantitative research methods. The study population of students in extracurricular futsal totaling 30 people and all were taken as sample. Data collection techniques used is a practice test and, questionnaire and documentation. Data were analyzed using descriptive analysis and ordinal regersi test. The results showed there is a contribution agility with results dribbling skills 31.6%, there is a contribution durability with dribbling skills by 43.6%, there is a contribution confident dribbling skills of 16.7%, there were contributions agility and endurance with dribbling skills by 49.2%, there were contributions agility and confidence in dribbling skills by 33,The conclusion that the contribution of agility, endurance and confidence that both can affect the dribbling skills in the game of futsal are good also. By the evidence of this hypothesis it is expected to benefit particularly for coaches or players in order to improve the skills of dribbling game of futsal, it is necessary mastery of agility, endurance and the cultivation of good confident posture and maximum.